The impact of owner management on the financial performance of a company: a case of Hofstra Manacc Consultancy - Marodzah, Regai (Midlands State University, 2018)
This research seeks to examine the impact of owner management on the financial performance of a company using Hofstra Manacc Consultancy as a case study. Some scholars were of the view that ownership structure plays a significant role in determining the financial performance of a company. However, others argued that ownership and management structure of a company has nothing to do with the financial performance of a company. In conducting this research, the researcher used the mixed approach which encompassed both quantitative and qualitative methods of collecting data. Questionnaires were administered to eighteen respondents and four questions were asked in conducting interviews. The research findings showed that organisational structure, structure formalisation, structure complexity and structure centralisation greatly affect the financial performance of a company. It was also found that accounting practices by small firms and the knowledge of performance measurement play a vital role in determining a firm’s financial performance. The entity was then recommended to employ an expert manager, practice proper financial reporting as well as centralise decision making through delegation and consultations.